Perbandingan Laju Fotosintesis Pada Tanaman Yang Tumbuh Di Tempat Terang Dan Gelap - Debora Zega, Novita; Mendrofa, Elsa Greta; Gea, Chelsa Julian; Halawa, Lola Sri Wahyuni; Lase, Herni Susanti; Waruwu , Irwilan; Lase, Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This study was conducted to explore the differences in the rate of photosynthesis in plants growing in light and dark environments, focusing on corn (Zea mays) and mung bean (Vigna radiata). Photosynthesis is an essential process that allows plants to generate energy from sunlight, with light being a key factor that determines the efficiency of this process. In this study, the plants were grown in two different conditions: a light environment with direct sunlight exposure and a dark environment with no light exposure. Observations were made over a period of one month to record the morphological and physiological differences in the plants. The results showed that plants growing in the light environment had a higher rate of photosynthesis, indicated by fresh green leaves due to optimal chlorophyll formation.